Small fish powder - Sean, Vichet; Ou, Phichong (WorldFish, 2023)
Made from pounding small fish species that are often found in Cambodia, especially in the Mekong basin, small fish powder is a nutritional component. The purpose of this fish powder is to fight malnutrition, particularly in children between the ages of 6 and 23 months. Here are some more details on little fish powder in Cambodia: Nutrient-dense: Omega-3 fatty acids, calcium, zinc, zinc, protein, and small fish powder are all important for a child's healthy growth and development.